Bio-Waste Recycling in Germany – Further Challenges. (15th December 2017) - Schüch, Andrea; Morscheck, Gert; Lemke, Astrid; Nelles, Michael
ABSTRACT: German biodegradable waste is collected separately, recycled and ecologically and economically sound used. Around the world biodegradable waste in landfills is the main factor for greenhouse gas emissions. This environmental impact can be significantly reduced by the separate collection and use of organic waste. The separate collection of bio-waste is also a precondition for reutilizing of organic matter and nutrients. Only from separately collected bio-waste it is possible to produce high-quality compost and digestate, which are suitable for agricultural or horticultural use. The separate collection of bio-waste from households affects the amount and composition of the residual waste. By separating bio-waste, the remaining amount of waste is reduced up to a third. At the same time the residual waste contains less wet ingredients, which facilitate the waste sorting and makes the treatment in waste incineration plants more effective or even possible. Both, the recycling of compost and digestate on soils, as well as the energy recovery of bio-waste, contribute to climate protection and resource conservation. The operation of the treatment plants determines how much of the greenhouse gases methane, nitrous oxide and ammonia is released during the process. Some plant operators need to be awakened and their awareness of climate-relevant emissions from their bio-waste treatment plants has to be raised. Also the amount of collected organic waste should be further reinforced. In Germany since 2015 the separate collection of bio-waste has to improve!